Controlling BP is Critical for People with CKD - Nierengarten, Mary Beth (MD Conference Express, 2014)
This article discusses the critical need to control blood pressure (BP) for patients with chronic kidney disease, issues in diagnosis and management, and specific issues in patients with end-stage renal disease.